2021
DOI: 10.47672/ajep.705
|View full text |Cite
|
Sign up to set email alerts
|

The use of Constructivists’ Approach in Teacher Preparation; A case of Primary Teachers Colleges of South Eastern Uganda

Abstract: Purpose: The purpose of this study was to explore the implementation of constructivists’ principles in teacher preparation in colleges and to establish whether the constructivist approaches were being used to teach students. Methodology: This phenomenological study explored the lived experiences of tutors and students in light of constructivists informed teaching. It involved 3 PTCs and 15 participants who were purposively sampled. The methodology for this study was qualitative with a phenomenological re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The theory of constructivist learning explains how people can acquire knowledge and learn, and it suggests first of all that "humans construct knowledge and meaning from their experiences" (Bada, 2015, p. 66). A study on the constructivist approach in teacher preparation conducted in Uganda by Gusango et al (2021) supports this theory of learning in teacher development. They concluded that the informed teaching of constructivists supports teaching effectiveness and promotes student learning, thus amplifying the need for reflective practice in instruction.…”
Section: Theoretical Frameworkmentioning
confidence: 76%
“…The theory of constructivist learning explains how people can acquire knowledge and learn, and it suggests first of all that "humans construct knowledge and meaning from their experiences" (Bada, 2015, p. 66). A study on the constructivist approach in teacher preparation conducted in Uganda by Gusango et al (2021) supports this theory of learning in teacher development. They concluded that the informed teaching of constructivists supports teaching effectiveness and promotes student learning, thus amplifying the need for reflective practice in instruction.…”
Section: Theoretical Frameworkmentioning
confidence: 76%
“…For instance, a child in such a school will take on a science combination but will never have access to any laboratory equipment, which leaves that child concentrating on imaginary scientific knowledge and skills. To illuminate this issue; a number of students know that a combination of hydrogen and oxygen yields water but how these atoms are combined remains mystery (Gusango et al, 2021). Are these not the many low cadre healthcare providers hovering the country and beyond, and can anyone insist that we are teaching more sciences (it is now compulsory at lower secondary schools in Uganda) than humanities that our leaders continually scold in virtually any speech?…”
Section: The Triggers Of Csw In Contemporary Ugandamentioning
confidence: 99%